Autophagy-dependent ferroptosis drives tumor-associated macrophage polarization via release and uptake of oncogenic KRAS protein. Issue 11 (1st November 2020) - Dai, Enyong; Han, Leng; Liu, Jiao; Xie, Yangchun; Kroemer, Guido; Klionsky, Daniel J.; Zeh, Herbert J.; Kang, Rui; Wang, Jing; Tang, Daolin
ABSTRACT: KRAS is the most frequently mutated oncogene in human neoplasia. Despite a large investment to understand the effects of KRAS mutation in cancer cells, the direct effects of the oncogenetic KRAS activation on immune cells remain elusive. Here, we report that extracellular KRAS G12D is essential for pancreatic tumor-associated macrophage polarization. Oxidative stress induces KRAS G12D protein release from cancer cells succumbing to autophagy-dependent ferroptosis. Extracellular KRAS G12D packaged into exosomes then is taken up by macrophages through an AGER-dependent mechanism. KRAS G12D causes macrophages to switch to an M2-like pro-tumor phenotype via STAT3-dependent fatty acid oxidation. Consequently, the disruption of KRAS G12D release and uptake can abolish the macrophage-mediated stimulation of pancreatic adenocarcinomas in mouse models. Importantly, the level of KRAS G12D expression in macrophages correlates with poor survival in pancreatic cancer patients. These findings not only identify extracellular KRAS G12D as a key mediator of cancer cell-macrophage communication, but also provide a novel KRAS-targeted anticancer strategy. Abbreviations: DAMP, damage-associated molecular pattern; PBMCMs, peripheral blood mononuclear cell-derived macrophages; PDAC, pancreatic ductal adenocarcinoma; s.c., subcutaneously; TAMs, tumor-associated macrophages; TME, tumor microenvironment.